1975
DOI: 10.2118/5059-pa
|View full text |Cite
|
Sign up to set email alerts
|

Denuding Hydrocarbon Liquids of Natural Gas Constituents by Hydrate Formation

Abstract: Hydrate formation from gases dissolved in hydrocarbon liquids partially strips lighter components from the liquid phase. Experiments demonstrate why Alaskan North Slope crude oils found below the permafrost can be expected to be denuded of a substantial portion of their dissolved gases. Introduction Gas hydrates are crystalline, ice-like solids formed when certain light hydrocarbons and other low-molecular-weight, nonpolar substances are contacted with water.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Katz and co-workers (7) have suggested that structure I and II hydrates might act to denude oil of viscosifiers, in known instances of "dead" highly viscous oil found associated with hydrates in natural permafrost regions. The size of the structure H large cavity and the phase equilibrium conditions both suggest that structure H hydrates may find applications in preferential denudation of light petroleum components.…”
Section: Resultsmentioning
confidence: 99%
“…Katz and co-workers (7) have suggested that structure I and II hydrates might act to denude oil of viscosifiers, in known instances of "dead" highly viscous oil found associated with hydrates in natural permafrost regions. The size of the structure H large cavity and the phase equilibrium conditions both suggest that structure H hydrates may find applications in preferential denudation of light petroleum components.…”
Section: Resultsmentioning
confidence: 99%
“…Katz and coworkers (Verma et al, 1975) suggested that sI or sII hydrates might act to denude oil of viscosifiers, in known instances of "dead" highly viscous oil found associated with hydrates in natural permafrost regions. Both sH hydrate phase equilibria conditions and the sH large cavity size suggest that sH hydrates are also likely candidates for the removal of light components from petroleum.…”
Section: Resultsmentioning
confidence: 99%
“…Gas hydrates may be formed not only from a hydrocarbon vapor phase but also from a liquid one (Katz, 1972;Verma et al, 1975; Holder et al, 1976). In this case, the hydrate formation may denude the oil in the reservoir from its light hydrocarbons.…”
Section: Technological Aspectsmentioning
confidence: 99%